Index to Proceedings of the Security Council: Seventieth Year, 2015 - United Nations (United Nations, 2016)
The Index to Proceedings of the Security Council is a bibliographic guide to the proceedings and documentation of the Security Council. This issue covers the seventieth year of the Council including its commissions, committees and ad hoc committees. The Index is divided in two parts comprising the Subject Index and Index to Speeches. The Index is prepared by the Dag Hammarskjöld Library, Department of Public Information, as one of the products of the United Nations Bibliographic Information System (UNBIS).